Legal Philosophy in Construction Contract Dispute Resolution: Between Arbitration and Litigation - I Wayan Lastikayasa; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
Disputes in construction contracts are a common occurrence due to project complexity, differing interpretations of clauses, and delays in work execution. In practice, two main dispute resolution paths are often chosen: arbitration and litigation. This study stems from the need to examine these dispute resolution mechanisms not only from a procedural perspective but also from a legal philosophy perspective that emphasizes the values ​​of justice, legal certainty, and expediency. The purpose of this study is to understand how legal philosophy can serve as a basis for selecting and assessing the effectiveness of arbitration and litigation as forums for resolving construction contract disputes. This study uses a juridical-normative method with a qualitative approach, supported by a comparative analysis of regulations, arbitration and court decisions, and relevant legal philosophy literature. The analysis shows that arbitration emphasizes efficiency, confidentiality, and procedural flexibility, thus closer to the values ​​of expediency and legal certainty. Conversely, litigation offers formal legitimacy, transparency, and broader legal protection, reflecting the values ​​of formal justice. However, both have limitations: arbitration is often hampered by high costs, while litigation is often protracted. The selection of a dispute resolution mechanism in a construction contract should be based not only on practical aspects but also on philosophical considerations regarding the objectives of the law. Thus, the integration of justice, certainty, and expediency can serve as a primary guideline in determining the most appropriate dispute resolution forum